Synergistic Effect of Electrolyte and Electrode in Nickel Cadmium Aging Battery Performances - Mohd Najib, Razali; Mohd Sabri, Mahmud; Syahirah Syazwani, Mohd Tarmizi; Mohd Khairul Nizam, Mohd Zuhan (Springer Nature Singapore, 2024)
The number of charge and discharge cycles that the battery can complete before losing its performance is called a battery life cycle. The life cycle of a battery is one of the important aspects in making sure the whole system process runs smoothly within the expected timeline. Each of the batteries has a different range of life cycle depending on their type, brand, materials of the batteries and how it is used. Several tests were conducted to compare the performance of the batteries used in the system. There were three parts of this performance test which are analyzing the physical characteristics of the Nickel–Cadmium battery, conducting characterization on electrolyte, and conducting the characterization on the electrode of the batteries which includes pH, conductivity, ICP-OES and BET analysis. The physical characteristics were based on the features and benefits of the batteries and also their technical specifications. In this study, the aging battery performances of three different rechargeable energy storage system: Battery A, Battery B, and Battery C. Each battery represents a distinct. From the result, Battery A showed the best aging battery performances compared to B and C Batteries. Battery A had the highest conductivity value and surface area from the tests conducted.